Material and immaterial. Ecological transition, training, places and educating communities - Cristian Righettini (Formare, 2024)
The contribution in question intends to reflect, without claiming to be exhaustive, on the ability of environmental pedagogy to connect the perspective of the ecological transition with training in sustainability skills, paying particular attention to people, without forgetting the places of education and socio-environmental communities. It is important to connect material and immaterial in the pedagogical discourse to learn sustainability, between knowledge, skills and ethical beliefs embodied in the life contexts of each and every one, in an ecological and inclusive way, towards the long-term well-being of people and the Planet. A commitment for today’s citizens and above all an educational legacy for the young generations, for the care of the common home, in its physical data and in its cultural and immaterial meanings.